2014
DOI: 10.2147/cia.s72521
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of low-dose oral prolonged-release oxycodone/naloxone for chronic nononcological pain in older patients

Abstract: PurposeChronic pain is highly prevalent in older adults. Increasing evidence indicates strong opioids as a valid option for chronic pain management in geriatrics. The aim of this study was to evaluate efficacy and safety of low-dose oral prolonged-release oxycodone–naloxone (OXN-PR) in patients aged ≥70 years.MethodsThis open-label prospective study assessed older patients naïve to strong opioids presenting with moderate-to-severe chronic pain. Patients were prescribed OXN-PR at an initial dose of 10/5 mg/day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 34 publications
1
26
0
1
Order By: Relevance
“…Major barriers to opioid use are opioid-related side effects [33]. The most common side effects are constipation, dizziness, nausea, vomiting, and delirium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major barriers to opioid use are opioid-related side effects [33]. The most common side effects are constipation, dizziness, nausea, vomiting, and delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Constipation is one major side effect of opioids. The use of oxycodone-naloxone can reduce the rate of constipation [33]. Duloxetine is a drug that can act on the central nervous system like opioids.…”
Section: Discussionmentioning
confidence: 99%
“…The oxycodone-naloxone prolonged-release combination has shown analgesic efficacy in studies, with a significant reduction in the incidence of opioid-induced constipation and improvement in patient quality of life 37,39,40 . A study conducted by Guerriero et al 37 demonstrated statistically significant clinical improvements during oxycodone-naloxone treatment.…”
Section: Oxycodonementioning
confidence: 99%
“…Limits of opioids use in this population are represented by a higher incidence of opioid-related side effects. 60 62 A 4-week, single-center, prospective observational study investigating the analgesic efficacy and tolerability of PR OXN in patients older than 70 years naïve to strong opioids was published by Guerriero et al 63 The effects of PR OXN on functional and cognitive status, mood, and quality of life were also analyzed. Twenty-six percent of the patients enrolled in this study complained of constipation at baseline, but almost all had BFI values >29, indicating some degree of bowel dysfunction.…”
Section: Oxycodone–naloxone In Older Patientsmentioning
confidence: 99%